The Effect On Male Rats’ Reproductive Function After Longterm Administration Of Methamphetamine Hhydrochloride And Its Withdrawal - Yusof, Muhammad Fuad Hilmi (2009)

(untitled)
This experiment investigate the effect of methamphetamine hydrochloride (MA HCl) administration and its withdrawal on the male rat reproductive functions. We studied the serum gonadotrophins which are follicle stimulating hormone (FSH), luteinizing hormone (LH) and testosterone, relative reproductive organs weight, testis morphology and sperm count and sperm morphology.